Workplace violence: A comprehensive look at OSHA recordkeeping - Sweet, Abigail Marie (East Carolina University, 2017)
Workplace violence is a major issue in many occupations. Acts of workplace violence can cost companies millions of dollars. Using a workplace violence prevention programs to control workplace violence, could be vital in saving a company money and possibly saving someone's life. There are four types of workplace violence that could occur: criminal intent, customer/client, employee on employee, and personal relations. The purpose of this study was to describe and explore workplace violence incidents and describe their contents utilizing the United States Occupational Safety and Health Administration's Integrated Management Information System (IMIS) database in order to investigate the adequacy of the OSHA IMIS database to provide sufficient information in support of developing workplace violence prevention programs. OSHA is responsible for inspecting and describing catastrophic and fatal acts of workplace violence. Inspection data was reviewed and analyzed for the purpose of this study. The data showed that OSHA inspected fatalities with much more urgency than they inspected injuries and nonfatalities. Forty-four out of the fifty workplace violence fatalities that were analyzed were inspected by OSHA within seven days of the fatality occurring, or 88 percent. Twenty-three out of fifty workplace violence nonfatalities and injuries were inspected within nine days of the incident occurring, only 46 percent. This leads to the conclusion that OSHA takes workplace violence fatalities much more seriously and there is not as much of a sense of urgency when it comes to workplace violence nonfatalities and injuries. A person being shot with a gun was the number one cause of workplace violence fatalities among the 100 incidents investigated. This accounted for sixty-eight percent of all workplace violence fatalities included in this research. Security measures should be implemented in highrisk occupations, such as bulletproof screens protecting the employees or providing security officers to protect the employees. These high-risk occupations include taxi drivers and late-night convenience store workers. The data collected for the purpose of this research identified many inconsistencies and missing data within the 100 workplace violence event descriptions found on the IMIS database. This makes describing the data fully and drawing conclusions very difficult. OSHA inspectors should consider a more uniform approach when collecting variables at a particular scene, which would lend to a deeper understanding of workplace violence and potentially a more robust workplace violence program. This lack of information was a limitation in the research conducted. Workplace violence is a serious issue that countless employers and employees must deal with every day. There must be programs set in place, such as the one California has implemented and is having so much success with, in order to bring awareness to employees and employers about how to handle workplace violence and to teach them what to do in situations that could otherwise be harmful to them. OSHA must do a better job in describing the scenarios that they encounter in order to set up policies and procedures that are more comprehensive, which could be beneficial to the next company that may face workplace violence in setting up a workplace violence program.
Keywords: Violence in the workplace--United States; Industrial safety--United States; Employee health promotion--United States; United States--Occupational Safety and Health Administration--Statistics